(untitled) (Health Renaissance, 2017)
Aconitine and related alkaloids found in the Aconitum species are highly cardiotoxic and neurotoxic. The wild plant (especially the roots and root tubers) is extremely toxic. Severe aconite poisoning can occur after accidental ingestion of the wild plant or consumption of an herbal made from aconite roots. In traditional Chinese medicine, aconite roots are used only after processing to reduce the toxic alkaloid content. Soaking and boiling during processing will hydrolyze aconite alkaloids into less toxic and non-toxic derivatives. However, the use of a larger than recommended dose and inadequate processing increases the risk of poisoning. The aconite herb is one of the commonly-prescribed ingredients for various clinical problems. However, due to its narrow therapeutic index, toxicities are not uncommonly encountered, including life-threatening cardiac arrhythmias like ventricular arrhythmias Health Renaissance 2015; 13 (1): 108-111